Best practices in the registration process of barangay micro business enterprises law at the local government level in Metro Manila - Cabali, Pearl Grace Garcia (Animo Repository, 2007)
The Philippine government has se a policy to promote the establishment of BMBEs by providing various incentives and benefits to entrepreneurs. The BMBE Act of 2002 "Barangay Micro Business Enterprises Law" (BMBE Law) aims to hasten the country's economic development by encouraging the formation and growth of barangay micro business enterprises which effectively serve as seedbeds of Filipino entrepreneurial talents, and integrating those in the informal sector with the mainstream economy, through the rationalization of bureaucratic restrictions, the active intervention of the government specially in the local level, and the granting of incentives and benefits to generate much-needed employment and alleviate poverty.The Philippine government increasingly regards MSMEs as the diving force behind economic and social development. However, structural and institutional problems are hampering efficient and dynamic management at both national and regional level. The Micro, Small and Medium-size Enterprises (MSMEs) are struggling with a multitude of economic-policy, legal and bureaucratic obstacles. Among these are cumbersome license and regulatory procedures as well as insufficient access to markets, business services, training and upgrading and financial and credit services. The investment climate of the Philippines thus is not conducive to the full usage of entrepreneurial capacities of MSMEs. The Local Government Unit LGUs) play a significant role in encouraging business start-ups and providing a conducive environment for their growth so that they can generate more economic activities for the benefit of our local communities. They are tasked to implement the registration procedures of the BMBE Law. The law and the implementing rules and regulations allow the LGU to implement the laws according to its own interpretation. With this, the paper aims to identify the best practices being employed by the fourteen (14) cities in Metro Manila in effectively implementing the BMBE law and eventually other local government will be available to replicate these best practices.